Ambiguity in organization theory : from intrinsic to strategic perspectives - Cappellaro, Giulia; Compagni, Amelia; Vaara, Eero (Cambridge : Cambridge University Press, 2023)
This volume elaborates on the intrinsic perspectives on ambiguity as an inherent part of organizational decision-making processes and the more recent strategic perspectives on discursively constructed strategic ambiguity. It helps illuminate the path ahead of organizational scholars and offers new avenues for future research.
Also issued in print: 2023.
Includes bibliographical references.
Specialized.
Description based on online resource; title from PDF title page (viewed on January 30, 2023).
Keywords: Organizational sociology